PEMANFATAN TEKNOLOGI WEB SEBAGAI PENGUKURAN KINERJA PENDIDIKAN DI RUMAH SAKIT - Lilik Lestari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to analyze the use of web technology as a measurement of educational performance in hospitals. This study was conducted with a research and development approach to the Pulmonary Hospital Dr. Ario Wirawan (RSPAW) Salatiga. Data sources are informants (apprentices, facilitators, heads of installations, employees), events, and documents. The sampling method is simple random sampling and census. The type of data used is primary data.Data were analyzed by descriptive statistics. The results showed that thewebsite performance measurement information system based on balanced scorecard was successfully implemented. The performance measurement information system website is equipped with an interface program in the form of graphics and data export facilities, so that the data needed for the evaluation of the implementation of education, both in the framework of the preparation of future internship program development programs and accountability for its implementation.Keywords: Website, Education Performance, Balanced Scorecard